Revitalisasi Cucupatian melalui Pengembangan Bahan Ajar Bahasa Indonesia di Sekolah Dasar - Fahimah*, Fahimah; Fitriani, Maudiya; Rianta, I Gusti Kadek Agus; Sartika, Yana; Hanafi, M.; Luthfiyanti, Lita (Universitas Suryakanca, 2024)
This article describes the development of Indonesian language teaching materials based on cucupatian for grade IV elementary school students. This research uses an ethnopedagogical approach with in-depth interviews and direct observation. There are several results of this research. First, the Indonesian language teaching materials at SDN Teluk Tiram 2 currently do not include Banjar culture. Second, cucupatian can be included in the descriptive text material in chapter 6